Perlindungan Masa Depan AUD Melalui Rumah Pintar Yasmin (Studi Kasus AUD Berbasis Masyarakat TKI) - Nurias Zetya Nawang Lupi (Universitas Trunojoyo Madura, 2014)
The focus of this research is to find out how smart home efforts in protecting the future of children affected by parents who become TKI in community-based Gondang Legi TKI. This study used a qualitative approach with a case study strategy. Results: (1) protecting the future AUD through smart home in the district Yasmin Gondang Legi done through reading centers, play centers, computer centers, center stage and craft centers; (2) smart home program has not been able to reach the entire early childhood education in the district area Gondang Legi, but some AUD participating in learning activities in reading centers, play centers and center stage; (3) support from various parties, especially from central and regional government is very helpful for early childhood to make his choice to be independent even though much of the attention of the biological parent. Social commitment shown by the tutor and the manager is a form of support that is very huge implications for early childhood development.